1879
DOI: 10.5962/bhl.title.5040
|View full text |Cite
|
Sign up to set email alerts
|

Minute structure of the central nervous system of certain reptiles and batrachians of America

Abstract: * This apparent anomaly loses its force, as such, when one considers that the difference in thickness, between the enlargements, is small, and depends upon an increase of gray substance, corresponding with a difference in development between the two pairs of extremities greater than in the alligator. Gelatine Negative No. g. Griinow 2 Imh. Gelatine Negative No. lo. Grtinow 2 Inch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
1964
1964

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Under the experimental conditions of the studies reported here, the chromatinic material of short cells is much more aggregated than that of elongated cells, which would suggest a possible correlation between chromatin dispersion and cell growth. These observations are not in keeping with those on other bacteria in which continuously aggregated chromatin is observed (7,8,11,37); however, Glauert (18) has reported similar findings in Clostridium welchii and Lactobacillus acidophilus.…”
Section: Protoplasmic Constituentsmentioning
confidence: 53%
“…Under the experimental conditions of the studies reported here, the chromatinic material of short cells is much more aggregated than that of elongated cells, which would suggest a possible correlation between chromatin dispersion and cell growth. These observations are not in keeping with those on other bacteria in which continuously aggregated chromatin is observed (7,8,11,37); however, Glauert (18) has reported similar findings in Clostridium welchii and Lactobacillus acidophilus.…”
Section: Protoplasmic Constituentsmentioning
confidence: 53%